Comprehensive methodology for standardized ecotoxicological assessment of TiO2-based sunscreen leachates in aquatic environment - Nugnes, Roberta; De Negri Atanasio, Giulia; Perata, Elisabetta; Lertora, Erica; Dondero, Lorenzo; Robino, Federica; Tardanico, Francesca; Capelli, Cristina; Ghioni, Fabio; Cai, Tania; Gobbato, Dalia; Marciani, Norina; et al. (Frontiers in Toxicology, 2025)
IntroductionThis study evaluates the ecotoxicity of micro- and nano-sized titanium dioxide (TiO2), either as active ingredients or incorporated into sunscreen formulations in the aquatic environment, by proposing a leaching protocol simulating a realistic scenario of human immersion in freshwater and seawater.MethodsTo this aim, an ecotoxicological screening of micro- and nano-TiO2 active ingredients and incorporated into sunscreens was applied, by evaluating acute and sub-acute responses (bioluminescence and growth inhibition, immobilization, behaviour) in freshwater and marine bacteria, microalgae and crustaceans. Then, Ti concentration was measured in the leachates of sunscreens through Inductively Coupled Plasma mass spectrometry (ICP-MS).Results and discussionToxic effects (EC50s) were only found in microalgae and crustaceans exposed to TiO2 active ingredients. No toxicity occurred with sunscreens formulations, although significant algal growth inhibition was determined, likely due to TiO2 size rather than Ti concentration. By integrating a sunscreen leachate based methodology with a multi-species and multi-endpoint approach, this study introduces a novel ecosafety-oriented assessment of TiO2 providing realistic ecotoxicological evidence relevant to freshwater and marine environments.